Life imprisonment in New Zealand - Anderson, Jordan (Life Imprisonment in Asia, 2023)
In 2020, the High Court of New Zealand handed down the country’s first ever sentence of life imprisonment without parole. This unprecedented sentence was applied to the perpetrator of the 2019 Christchurch terror attack. Convicted of 51 murders, 40 attempted murders, and one charge of engaging in a terrorist attack, the sentencing of the Christchurch terrorist represented the first use of the most severe sanction available in New Zealand legislation. Considering the public discourse around the sentencing in this case, and the trajectory of the ‘law and order’ conversation in this country over the last three decades, this chapter examines the socio-political context of legislative developments that have affected life and indefinite sentences. While life imprisonment without parole has only been imposed in one case, the use of life imprisonment more generally has remained consistent, while the scope of other indefinite sentences and measures has expanded over time. The number of prisoners held on indefinite sentences has increased considerably over time: now constituting approximately 11% of the total prison population. This paper provides an outline of the use of life imprisonment in New Zealand, and locates it within this growing suite of indefinite sentences and measures available in this country.